Upaya Meningkatkan Motivasi dan Hasil Belajar Seni Budaya ( Musik) dengan Menggunakan Model Pembelajaran Mind Maping Melalui Aplikasi Mind Maple Pada Siswa Kelas XII IPA 3 di SMA Negeri 5 Bukittinggi - Handayani, Lucy (Jurnal Ilmu Sosial, Humaniora dan Seni, 2022)
This research is motivated by the lack of involvement of students in learning activities because the strategies used do not attract students' interest in mastering the material being taught. This study aims to determine the increase in students' abilities by using the Mind Maping Learning Model through the MindMaple Application in class XII IPA 3 academic year 2021-2022 SMAN 5 Bukittinggi. This research is Classroom Action Research, with the research subjects being class XII IPA 3 students at SMAN 5 Bukittinggi for the 2021-2022 academic year, with a total of 31 students consisting of 13 students and 18 female students. Based on this study, it appears that an increase occurred in the class average score and the percentage of completeness of student learning outcomes. During the implementation of cycle I, the average score was 73. Out of 31 students who got 1 person or 3% Very Good score, 11 students or 35.4% who got a Good score, 6 people or 19.3% got Enough score, while those who got less scores were 13 people or 42% in this case meaning that the mastery level of new students reached 38% with student activity of 71.88. Whereas in cycle II the average value was 80 and of the 31 students in class XI IPA 5 who got a score with very good criteria was 0 or 0%, the score with good criteria had increased by 31 people or 100% and this means All students have received a minimum completeness score of 78. The level of mastery of students' knowledge of the material is 100% with student activity of 92.86.